Study of palm biomass ash as a supplementary cementitious material in concrete production (Research, Society and Development, 2021)
The valorization of by-products and/or waste from different production chains has been shown as an alternative in the incorporation as supplementary cementitious material (SCM), either in the production of cement, in addition, or replacement to the cement matrix. Such studies are important since the search for sustainable materials and less impactful to the environment is growing. Thus, this work aims to contribute to the study of new MCS through the use of ash from palm oil extraction waste, since such waste (mesocarp fiber, endocarp, and empty clusters) are used as biomass in the boilers of processing and refining of palm oil, generating large amounts of ash. To analyze the technical feasibility of this material, conventional concrete was produced as a substitute for Portland cement at 7.5% and 15%. The dosage method used was IPT/EPUSP and the water/binder ratio was set at 0.45 and 0.60. A reference mix (without replacement) was adopted for the concrete and the evaluation of mechanical properties was performed through strength tests (axial compression, tension by diametrical compression, flexural tension, and modulus of elasticity), where it was possible to observe that in compression strength the concrete with replacement did not overcome the strength obtained by the reference mix, but achieved similar results with the 15% substitution content associated with a water/binder ratio of 0.60. Moreover, it was possible to verify that the tensile strength and modulus of elasticity did not show significant results influenced by the ash content.